PENGARUH KEPEMIMPINAN, MOTIVASI DAN INSENTIF TERHADAP KINERJA KARYAWAN - Joannov, Joannov; Ernanda, Yovie (JEBIM Prima, 2022)
This study aims to examine and analyze the influence of leadership, motivation, and incentives on employee performance at PT. Tamoratama Prakarsa, Medan. A research method is a quantitative approach, this type of research is quantitative descriptive and the nature of this research is explanatory descriptive. The data analysis method is multiple linear regression analysis. The sample of this research is 63 employees. Partially, leadership has a positive and significant effect on employee performance at PT. Tamoratama Prakarsa, Medan. It can be seen from the value of thitung > ttabel or 2,746 > 2,001 and the significant obtained is 0,008 < 0,05. Partially, work motivation has a positive and significant effect on employee performance at PT. Tamoratama Prakarsa, Medan. It can be seen from the value of thitung > ttabel or 2,206 > 2,001 and the significant obtained is 0.000 < 0.05. Partially incentives have a positive effect on employee performance at PT. Tamoratama Prakarsa, Medan. It can be seen from thitung > ttabel or 2,128 > 2,001 and the significant obtained is 0,037 < 0,05. Simultaneously leadership, work motivation, and incentives have a positive and significant effect on employee performance at PT. Tamoratama Prakarsa, Medan seen from the value of Fhitung (11.402) > Ftabel (2.76) and a significance probability of 0.000 < 0.05.